Evaluating Soil Loss for Identification of Land Risk Area in the Kabe Watershed of Ethiopia - Fikru Assefa; Eyasu Elias; Teshome Soromessa; Abreham Berta Aneseyee (Applied and Environmental Soil Science)
Soil erosion is the main cause of topsoil loss in farming land, which results in reduction in cropland productivity. Soil loss estimation is crucial for developing soil and water conservation strategies for Ethiopia. The investigation aimed to estimate the soil loss in various intensifications of land use patterns, including slope categories, using the soil estimation model associated with the ArcGIS process. It is analyzed in Ethiopian conditions based on erosivity, soil erodibility, vegetative cover (C) remote sensing data, slop-length factor (LS), and management practices (P). The mean soil loss was relatively high (20.01 t ha−1yr−1) in the cultivated land, whereas it was lowest (0.17 t ha−1yr−1) under forest land. Soil loss in the watershed shows a significant variation under slope classification. Moreover, the land having a greater slope angle, or the upper slope of the watershed, contains maximum soil erosion, while the lower slope position has a minimum soil erosion rate. The validation shows that there is an insignificant variation between the predicted model and the experimental data. Therefore, this confirms that the model can be applied in the study watershed or elsewhere with similar agroecology to the study area. This research is also used to prepare an erosion management strategy for the conservation of soil and water in the watersheds.